Research, the Builder of Markets - Rishell, Carl (Indian Forester, 1946)
The author of this article sees research as the only means of enabling wood to hold its own in competition with other materials suggestions are made for a research program that would emphasize particularly (1) improvement in lumber and lumber products and (2) utilization of wastes in the woods and at the mill.